2017
DOI: 10.1063/1.4977768
|View full text |Cite
|
Sign up to set email alerts
|

High Ku and small grain size Co80Pt20 granular media with double oxide grain boundary materials consisting of B2O3

Abstract: Investigation of magnetic properties and microstructure of granular media with various double oxides including B2O3 as the grain boundary material is reported. By adding a high Tm second oxide together with B2O3 for the grain boundary material, comparable magnetic properties with that of the single oxide granular media and smaller crystallite size evaluated by X-ray diffraction (GDinplane) than that of the single oxide granular media can be obtained. Among the evaluated media, the granular medium with B2O3− Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Generally, for the grain boundary materials, oxides material which do not dissolve into the CoPt metal, such as SiO 2 , 3 8,9 Furthermore, by mixing low T m B 2 O 3 with high T m oxides, media with small magnetic grain size can be obtained. 10 It is also shown that the introduction of a buffer layer (BL) underneath the granular media has a great impact on promoting the intergranular exchange decoupling of the media. 11 However, the relation between magnetic properties and T m in a Electronic mail: tham@ml.tanaka.co.jp the granular media with multiple oxides and the synergetic effect of BL and multiple oxides on the media have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, for the grain boundary materials, oxides material which do not dissolve into the CoPt metal, such as SiO 2 , 3 8,9 Furthermore, by mixing low T m B 2 O 3 with high T m oxides, media with small magnetic grain size can be obtained. 10 It is also shown that the introduction of a buffer layer (BL) underneath the granular media has a great impact on promoting the intergranular exchange decoupling of the media. 11 However, the relation between magnetic properties and T m in a Electronic mail: tham@ml.tanaka.co.jp the granular media with multiple oxides and the synergetic effect of BL and multiple oxides on the media have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…For a conventional hcp CoPt-oxide based granular medium deposited at RT, the non-magnetic oxides are precipitated at grain boundaries on the c-plane oriented Ru underlayer with a bumpy structure. [1][2][3] This prevents contact between the adjacent magnetic grains and realizes a columnar structure. The critical thickness of homogeneous granular structure along the thickness direction (d cri ), the amount of stacking faults (P fcc ), and K u are all strongly dependent on the melting point (T m ) of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…The CoCrPt (oxides) perpendicular magnetic anisotropy thin films have been applied in current perpendicular magnetic recording media for long periods of time but are still required to improve the properties in the near future [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Although ordered L1 0 -FePt with higher perpendicular anisotropy has been promised for future ultra-high density heat-assisted magnetic recording media [15][16][17], improvements of the intermediate-, exchange coupling-and capping-layer are needed to optimize the magnetic properties and microstructure of CoCrPt-oxide granular films for next-generation devices.…”
Section: Introductionmentioning
confidence: 99%